Veterinary Anthelmintics and Anthelmintic Drug Resistance - Dyary, Hiewa Othman (Sulaimani Journal for Pure and Applied Sciences, 2016)
Helminths are a diverse group of parasitic worms in the body of animals and human. Infection of livestock with parasitic worms poses a great burden on the health of animals that eventually leads to great losses in the productivity of these animals and economic losses to the farmers. The control of helminthiasis is dependent almost solely on the use of anthelmintic drugs, due to the ease of implementation and low cost of therapy, compared to other methods of control. However, chemotherapy of parasitic worms is burdened with such problems as the development of anthelmintic resistance (AR). Many of the currently available anthelmintic drugs have been in use for quite a long time and reports exhibiting the development of AR against them are increasing. Improving livestock management and, hence, productivity is a requirement in order to compensate for the increasing world population, which will eventually lead to increased demands for animal products. The tackling of AR needs to implement such methods as: (i) the systematic use of the currently available drugs, (ii) control of animal pasture, (iii) promoting the breeding of animals that are naturally resistant to certain types of helminths and (iv) development of new anthelmintic drugs by the pharmaceutical industry that have novel modes of action. Although each of these methods plays a part in the control program, chemotherapy will remain the cornerstone in the control program of helminth infections. Hence, the continuous supply of new antiparasitic compounds to the currently available anthelmintic pool is the best strategy to be implemented in the fight against helminth infections.
Keywords: Helminth; Anthelmintic drugs; Anthelmintic resistance